The Influence of the Principal's Servant Leadership Style and Contingency Factors on Student Achievement at Daarul Qur'an Kalibata Elementary School - Hani Islami; Dela Silmi Karmila; Hasyim Asy’ari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to investigate how the principal's servant leadership style and contingency factors affect student achievement at SD Daarul Quran Kalibata. The method used was qualitative with a case study design. Data were collected through in-depth interviews with the principal, a number of teachers, and parents, as well as through direct observation in the classroom and school area. To analyze the data, researchers used thematic analysis, which allowed them to find patterns in the interaction between the principal's leadership style, contingency factors, and student learning outcomes. The findings from this study show that the principal's application of servant leadership style, which emphasizes service and attention to the needs of team members, has a positive impact on student motivation and performance. In addition, contingency factors such as support from parents, social environment and students' motivation have a great influence on their academic performance. The study concludes that educational success depends not only on leadership style, but also on external factors that support students' learning process. The suggestion from this study is for principals to continue developing a service-based leadership style as well as improving communication with parents and other supporting factors to boost student achievement at school.